PENINGKATAN KEMAMPUAN MENULIS TEKS EKSPOSISI DENGAN MEDIA PEMBELAJARAN BERBASIS KEARIFAN LOKAL SUKU BATAK PADA KELAS X SMA EKA PRASETYA MEDAN - Nenny Triana Hutagalung; Kristiawan Indriyanto; Esra Perangin-angin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to improve the ability to write exposition texts of class X students at SMA Eka Prasetya Medan through the application of learning media based on local wisdom of the Batak Tribe. This study was motivated by the low writing skills of students, as indicated by the results of daily tests that were still below the Minimum Completion Criteria (KKM). The method used was Classroom Action Research (CAR) which was carried out in two cycles. In each cycle, the researcher implemented a learning strategy that was designed in stages, with a focus on improving the learning approach, providing more specific feedback, and increasing the intensity of writing exercises and group discussions. The results showed a significant increase in students' writing skills. In cycle I, only 17.65% of students achieved scores above the KKM, while in cycle II, the percentage increased to 87.35%. These findings prove that the use of local wisdom-based media is effective in improving the ability to write exposition texts and strengthening students' understanding of the structure and content of the writing.